Laparoscopic transduodenal ampullectomy: initial experience from a single center - Gao, Pan; Cai, He; Wu, Zhong; Peng, Bing; Cai, Yunqiang (Frontiers in Oncology, 2023)
Background: Laparoscopic transduodenal ampullectomy (LTDA) is a function-preserving surgery for premalignant tumors of the ampulla of Vater (AoV). However, it is technically challenging, and only a few case reports of LTDA are available in the literature. Methods: A total of 43 cases of pre-malignant tumors of AoV were operated in West China Hospital, Sichuan University-between January 2017 to July 2022. Among these patients, nine patients (group 1) underwent LTDA, nineteen patients (group 2) underwent laparoscopic pancreaticoduodenectomy (LPD), and fifteen patients (group 3) underwent open transduodenal ampullectomy (OTDA). Prospective collection and retrospective analysis of the demographic characteristics, intra-operative variables, and postoperative variables were carried out. Results: The patients in three groups were comparable in terms of sex, age, body mass index, tumor size, and preoperative blood tests. In comparison to the patients in group 2, the patients in group 1 were found to require less operative time (159.7 ±47.5 min vs. 298.1 ±62.6, p < 0.01) and suffered lower blood losses (23.3 ±16.7 mL vs. 156.8 ±112.1, p = 0.002) and complications. Moreover, the postoperative hospital stays (POHS) were significantly shorter for patients in group 1 (9.0 ±5.3 days vs. 15.5 ±7.3 days, p = 0.04). Compare to patients underwent OTDA, the patients in LTDA suffered from less blood loss. The operative time and post-operative details were comparable. Conclusions: Therefore, LTDA was found to be safe and feasible in the setting of pre-malignant tumors of AoV in well-selected patients. However, multidisciplinary preoperative planning is essential before the surgery.